Bucin (Budak Cinta): The Other Side of Love Addiction in Romantic Relationships in Indonesia - Muhammad Fath Mashuri; Andi Ika Patriasih (Universitas Islam Tribakti Lirboyo Kediri, 2023)
The phenomenon of budak cinta (bucin) in the romantic relationships of Indonesian adolescents requires partners to make sacrifices. It becomes crucial because it produces some negative impacts. The researcher explores the causal factors, behavioral patterns, and impact of bucin behavior. The model of the approach chosen is indigenization from within using two types of quantitative and qualitative analysis. This study showed that 78.3% of respondents had experienced bucin. Then the level of education, duration of relationships, and influence of the social environment can be factors in the tendency of individuals to behave bucin. In addition, this study formed several themes that raised the causative factors, behavioral forms, and impact of bucin when they were in a dating relationship. These three things are arranged based on a subtheme, which provides an overview and understanding of the conditions behind bucin behavior.